Automatic curtain / Ahmad Khairuddin Ariffin and Ahmad Shahir Zainal Othman - Ariffin, Ahmad Khairuddin (2005)
In this semester’s K.EU 280 project we are required to create an Automatic Curtain system. This project is a part of a mother program called SMART HOME where the Automatic Curtain system will be implemented in the program. The main idea of this project is to create an automatic curtain that will pull close or open automatically according to the photo-sensor’s signal as the main switch to operate the curtain. With the implementation of this project, the user from now on addressed as the consumer will benefit from the characteristics of the curtain where it is pulled close or open independently without having to be taken care of by the consumer on daily basis. Therefore, the consumer can spend more time on other household chores. From the home-security point of view, the automatic curtain successfully matched the criteria of home safety and security as the curtain automatically closes at night time. When the morning rises, it will pull open allowing the sun ray to shine into the house. Thus, acting as a natural alarm clock to awaken the sleeping residents, who are irritated by the sunshine. The automatic curtain system works on every type of curtains and windows. The fact is due to the system that only mobilizes the curtain without having the fabric of the curtain or the window type as an installation completion factors.